2005
DOI: 10.1071/ch05226
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Ammonium Arylspiroborate Esters as Organo-Soluble, Environmentally Benign Wood Protectants

Abstract: As part of a larger project aimed at the development of leach resistant boron-based wood preservatives, the anti-fungal and termiticidal activities, and the resistance to leaching from timber, of three related tetra-n-butylammonium spiroborates, tetra-n-butylammonium bis(ortho-hydroxymethylphenolato)borate 2, tetra-n-butylammonium bis[catecholato(2–)-O,O′]borate 3, and tetra-n-butylammonium bis[salicylato(2−)-O,O']borate 4, have been examined. All three borates are found to be active against test organisms, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…1. [7,8] All three of these esters were found to be more resistant to aqueous leaching from timber than boric acid, with the salicylate, 3, performing best in this regard. The complexation of borate in this way was expected to lead to a drop in biocidal activity, [5] as it should restrict the release of the biologically active free borate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1. [7,8] All three of these esters were found to be more resistant to aqueous leaching from timber than boric acid, with the salicylate, 3, performing best in this regard. The complexation of borate in this way was expected to lead to a drop in biocidal activity, [5] as it should restrict the release of the biologically active free borate.…”
Section: Introductionmentioning
confidence: 99%
“…[8] correlated with lipophilicity rather than susceptibility to hydrolysis, whereas leach resistance correlated with hydrolytic stability rather than lipophilicity. It was concluded that important timber preservative properties such as permanence, delivery to the biological site of action in the wood decaying organism, and activity at this biological site have conflicting physiochemical requirements, and the best preservative will meet a balance between these properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not the case for wood treatments where the CSIRO-New Zealand joint venture ENSIS has its own testing facilities. Carr, Duggan, Humphrey, Platts, and Tyndall [15] have used these facilities to show that environmentally benign boron compounds are both effective fungicides and can be made leach-resistant.…”
Section: Tom Spurling Joined the Csiro Division Of Applied Chemistry mentioning
confidence: 99%